DESIGN OF SYSTEMS AND FORMS, METHODS AND TECHNIQUES OF AESTHETIC EDUCATION OF JUNIOR SCHOOLCHILDREN TOOLS AND DESIGN - M.V. Ganja (Academy of Cognitive and Natural Sciences, 2022)
Forms, methods and receptions, are examined in the article, that take into account the features of design facilities in aesthetic education of junior schoolboys. The necessity of system their use is underlined in the process of aesthetic education students of initial classes